Exploring the impact of the COVID‐19 pandemic on cardiac surgical services: A scoping review. Issue 9 (16th June 2021) - Shah, Syed Muhammad Ismail; Bin Zafar, Muhammad Daim; Yasmin, Farah; Ghazi, Erum Mir; Jatoi, Hafsa Nazir; Jawed, Areesha; Nadeem, Areeba; Khan, Zarlish; Anas, Zahra; Siddiqui, Sarush Ahmed
Abstract: Cardiac surgery was severely affected by the COVID‐19 pandemic. Reallocation of resources, conversion of surgical intensive care units and wards to COVID‐19 facilities, increased risk of nosocomial transmission to cardiac surgery patients, lead to reduced accessibility, quality, and affordability of health care facilities to cardiac surgery patients. Increasing the mortality and morbidity rate among such patients. Cardiac patients are at an increased risk to develop a severe illness if infected by COVID‐19 and are associated with a high mortality rate. Therefore, measures had to be taken to reduce the spread of the virus. Various approaches such as the hubs and the spokes centers, or parallel system were enforced. Elective surgeries were postponed while urgent surgeries were prioritized. Use of personal protective equipments and surgeries performed by only senior surgeons became necessary. Surgical trainees were also affected as limited training opportunities deprived them of the experience required to complete their fellowship. Some of the trainees were reallocated to COVID‐19 wards, while others invested their time in research opportunities. Online platforms were used for teaching, meetings, and workshops across the globe. Although some efforts have been made to reduce the impact of the pandemic, more research and innovation is required.